EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN WORTEL (Daucus carota L.) DI KECAMATAN SIRAMPOG KABUPATEN BREBES JAWA TENGAH - Falahudin, Sefa; Nugroho, Yudha Sakti; Prastya, Rofiq Agiel; Afria, Fendra (Jurnal Tanah dan Sumberdaya Lahan, 2024)
The characteristics and quality of soil can affect the suitability of a land for a certain type of land use. The quality of the soil itself has a close relationship with the characteristics of the land because it has a score weight that affects the suitability of the land. Land characteristics such as slope and land cover affect soil quality such as nutrient content. Erosion calculations using the USLE method show that slope and land cover affect the rate of erosion, where erosion can leach nutrients that result in decreased soil quality. This study aims to determine the suitability of land for carrot plants in Sirampog District. Sirampog District has suitable marginal to suitable temperature, suitable humidity and rainfall, suitable soil texture (loam, sandy loam, and silty loam) relatively low cation exchange capacity (CEC) with very high base saturation, acidic soil pH, medium C-organic, medium N-total, very low P2O5 and very low K2O. This study provided an evaluation of land suitability so that farmers use effective and efficient techniques in cultivating carrot plants, so that carrot crop productivity can be optimal.